Islamic History: a Framework for Inquiry (Studies in Middle Eastern History, No. 9) by R. Stephen Humphreys; Minneapolis: Bibliotheca Islamica, 1988, 375 pp. (American Journal of Islam and Society, 1989)
Stephen Humphreys' Islamic History: a Framework for Inquiry representsa new approach to the old problem of the historian and his sources. Followingthe current trend among Western scholars ofislam and of history in general,Humphreys 'lays much more emphasis on the methodology of dealing withpre-modern historical sources than on establishing the "facts" to get at the"truth." This is because of Humphreys' belief, widely shared by historianstoday, that before we can learn any facts, we must understand our sources,their uses and their inadequacies, and that before we can understand the sources,we must arrive at a methodology that is universally acceptable, at least inits broad outJine. With reference to mecljeval Islamic history, these needsare all the more acute, because there has been little systematic thought givento methodology, except in a few introductory pages in the work of certainscholars, and because the sources themselves present so many problems.Owing to these considerations, Humphreys' book focuses on methodology,contains no narrative history and is intended for the student of history orone of its allied fields rather than the layman. The book covers the periodof medieval Islamic history, which is defined as 600-1600 CE. The reasonfor continuing to use this conventional and widely-accepted division is thatthe source material fundamentally changes in quality for the period after1500 because of the survival of Ottoman archival material subsequent to thatdate (p. 9). This seems reasonable, for the lack of contemporary documentsfor the medieval Islamic period imposes a greater reliance on non-literaryepigraphic and archaeological evidence, as well as traditional literary sourceswhich are usually not contemporary with the events described, leading intum to a different methodology than that of modem social science. On theother hand, one must remember that the study of history should not molditself simply according to the dictates of what is and is not available in thesources, for that could exaggerate the distortions to which our informationis already subject. AJso, we should not forget that artificial periodizationsmay obscure the real continuity of the flow of history and impair our abilityto see its unifying features. Nevertheless, the atomization of history did notbegin with Humphreys, whose methodology rather tends to unify Islamichistory by seeing similar patterns in and drawing comparisons between widelydivergent times and places.To demonstrate his methodology, Humphreys divides his work into twoparts. The first part consists of two chapters covering modem reference worksand the medieval sources of evidence generally, while the second part containsten chapters. each dealing with a broad problem of Islamic history and detailingthe sources relevant to that problem. Humphreys' strong bibliographicalemphasis makes his work most closely resemble Jean Sauvaget's Introductionto the History of the Muslim East (Berkeley and Los Angeles: Universityof California Press, 1965), as revised by Claude Cahen, a work whichHumphreys himself refers to as "the best overview we have of Islamic historicalstudies" (p. 20) . Sauvaget, however, was selective, whereas Humphreys aimsto be comprehensive, and to a large extent succeeds. Because it is both broaderand more recent, Humphreys' work supersedes the earlier book. As a generalannotated bibliography, Humphreys' work is certainly a useful resource forstudents of Islamic history ...